Faktor – Faktor Yang Berpengaruh Terhadap Kebijakan Hutang Perusahaan (Studi Empiris pada Perusahaan Maufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Yenniria Nurhaidah; Ronny Malavia Mardani; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine and analyze the factors that affect the company's debt policy partially. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis with the help of SPSS software version 14 (Statistical Products and Service Solutions version 14). Research samples of 41 companies were taken by purposive sampling method. This type of research is causality.The results of this study show that partially Free Cash Flow has a negative and significant effect on The Debt Policy, while managerial ownership and dividend policy have no effect on the Debt Policy, and the Company Size has a positive and significant effect on the Debt Policy. Keywords: Free Cash Flow, Managerial Ownership, Dividend Policy, Company Size, and Debt Policy.